Pascal: «une trace / la trace» in the concept of man in postmodern French philosophy - Kutsepal , Svitlana (Sententiae, 2000)
The article reconstructs the image of man in French postmodern philosophy of the second half of the twentieth century. The formation of this image is considered in relation to Michel Foucault's concept of sciences, as well as to the concept of schizoanalysis formulated by Gilles Deleuze and Felix Guattari. The author emphasizes that the key features of this image of a man are: (1) objectivity (modern culture makes a man not only a subject but also an object of science; therefore, the subject is presented not as a pure cognitive instance but also as a finite man limited in each specific historical epoch to specific forms of body, needs, and language); (2) emancipation as the content of freedom (a truly free person is seen as having left the sphere of existence as a machine – a set of functions). The author also notes that in the image of man associated with French postmodern philosophy, we can see a "trace" of Pascal's ideas about the duality of man and the impossibility of reducing him to any single aspect of his nature and existence, including rational or animal ones.